Interpretation of Tawhid Rububiyah in the Qur'an Surah Al-Fatihah: Study of Tafsir Ijmali - Muhammad Firman; Muhammad Frandika; Zulkifli; Edi Hermanto (Konsultan Jurnal Ilmiah Indonesia, 2024)
Surah Al-Fatihah, as the opening of the Al-Quran, contains a deep meaning that covers various aspects of faith, including Tauhid Rububiyah. This research aims to explore the interpretation of Tauhid Rububiyah in Surah Al-Fatihah using the ijmali interpretation methodology. Through analysis of the verses of Al-Fatihah, especially the second verse,